The Impact of European Employment Strategy in Greece and Portugal Europeanization in a World of Neglect - Zartaloudis, Sotirios; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Through the new use of new empirical evidence derived from analysing employment services, gender equality policies and flexicurity in Greece and Portugal, this book provides compelling new insights into how European Employment Strategy (EES) can influence the domestic employment policy of European Union member states.
Keywords: Political science; Public policy; Europe -- Politics and government; European Union; Social policy; Social structure; Social inequality; Political Science and International Relations; Political Science; Social Policy; European Politics; European Union Politics; Public Policy; Social Structure, Social Inequality